A study on the effect of biconvex compact shape factors on prediction of dilution potential from tensile strength–compaction force data of coprocessed diluents - Salim, Ilyasu (2023)
The sample data shown in Table 1 reflects drug-diluent binary mixture compacted at variable compaction forces but with the same punch tooling. The tested validity of Pitts model has shown a w/d ≥ 2.0 which was above the theoretical minimum acceptable value of 1.0. The shape factors decrease with increasing values of d, t, and w. Previous studies found only slight differences between the shape factors, however with ΦSh being slightly higher (Yohannes and Abebe 2021). Comparing the shape factors for the three models in this study, it was observed that ΦPt was slightly higher than ΦPz, but ΦSh differ significantly to as twice their values. Tukey’s multiple comparison test indicated statistically significant differences between the three shape factors (p < 0.05) (Table 2). The variability can be appreciated when both ΦSh and ΦPt were normalized with ΦPz. The shape factors ΦSh and ΦPt were higher than ΦPz by a factor of 2.4 and 1.2, respectively. Similar trend holds for all other compaction data.